Epithelia and Connective Tissue: A Team-Based Learning Module for Histology - James Brokaw; Keith Condon; Dale Saxon; Herbert Cushing (Association of American Medical Colleges, 2015)
Abstract Introduction This team-based learning (TBL) module is one of 10 in a four-credit-hour course entitled Basic Histology, which is intended primarily for graduate students seeking entry into medical school. As such, it is taught with the same depth and rigor as the first-year medical histology course at our institution and in many ways is the equivalent course. At the conclusion of the, students will be able to recognize and differentiate the different types of epithelia and connective tissue, describe their cellular and noncellular constituents, and relate the tissues' characteristic structural features to their function in health and disease. Methods Prior to coming to class, students study relevant learning materials (textbook reading assignments and class notes). In class, they demonstrate their understanding of the subject matter by completing an individual readiness assurance test (iRAT). The students then take a group readiness assurance test (gRAT), which is the same test as the iRAT but taken in small groups. Finally, they apply this knowledge to a series of group application exercises. The module takes approximately 2 hours to complete. Results This TBL module has been administered five times to a total of 157 students. Mean percentage-correct scores for the iRAT and gRAT were 86.2% and 99.3%, respectively. Students scored a mean of 81.9% on the group application exercises. Furthermore, 53.3% of students agreed or strongly agreed with the following statement: "Overall, I feel the TBL sessions helped my course grade." Discussion We have previously reported that TBL modules and traditional lectures produce comparable learning outcomes in histology, as measured by our end-of-unit multiple-choice exams. The students take the TBL process seriously, they study the relevant learning prior to coming to class, and they demonstrate a good understanding of the subject matter, as evidenced by their iRAT scores. The students also demonstrate effective teamwork, as evidence by their gRAT scores and, more importantly, their performance on the group application exercises. Students rarely miss TBL sessions as they seem to feel an obligation to their teammates.